FIRST DIRECT DATING OF LATE PLEISTOCENE ICE-WEDGES BY AMS - Vasil'chuk Y.K.; Vasil'chuk A.C.; Plicht J.V.D.; Jungner H.; Sonninen E. (My University, 2000)
We present the first direct dating by 14C-accelerator mass spectrometry of three Late Pleistocene syngenetic ice-wedges from the Seyaha cross-section. They are representative of permafrost with multistage ice-wedges from the North of Western Siberia. The most important result is the clear vertical age stratification of the ice, i.e. the old ice is located beneath the young. This shows that a timescale can be assigned to these ice-wedges penetrating down into the permafrost. The age of the ice shows a depth of not more than 3-5 m for frost cracking; water penetrated into the ice-wedges at that depth. The lower part of the ice-wedges from the Seyaha cross-section has been dated between 21000 and 14000 BP.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен